Bipolar ablation of refractory ventricular arrhythmias using a novel dedicated adapter. A multicenter study. (3rd October 2022) - Futyma, P; Bordignon, S; Imnadze, G; Peichl, P; Seidl, S; Kueffer, T; Chen, S; Zarebski, L; Martinek, M; Puererfellner, H; Kautzner, J; Reichlin, T; et al.
Abstract: Background: Bipolar ablation (BA) recently emerged as an alternative for treatment of ventricular tachycardia (VT) and premature ventricular contractions (PVC) refractory to a classic unipolar ablation (UA). Data on the use of available BA systems is lacking. Purpose: To determine feasibility, safety and efficacy of a novel BA adapter in consecutive patients with refractory VT/PVC undergoing repeat ablations. Methods: The study group consisted of consecutive patients with VT/PVC after failure of at least one standard UA who underwent redo procedures performed with a support of BA at six European centers. A second ablation catheter was connected in the position of a return electrode using a novel BA adapter. Results: Between March 2021 and March 2022 a total number of 19 patients after failed ablation attempts underwent redo procedure using a novel BA adapter (17 males, age 61±11, number of prior ablation attempts 2, 5±1, 6; range 1–7). The main indication for redo ablation was recurrence of frequent PVC (n=10), VT (n=8) or electrical storm (n=1). Fifteen patients underwent combined UA+BA procedure during redo ablation, whereas 4 remaining patients underwent BA only. Two patients required epicardial access. Mean procedural time was 157±77 minutes. The mean BA time was 367±245s (power 32±9W) and mean UA time was 349±290s (power 43±6W). Apart from 1 anticipated AV block there were no major complications. Minor complications included char formation at 8mm tip electrode and steam pop without sequalae in one VT patient. BA+UA led to acute elimination of clinical PVC/VT in 18 patients. In the remaining 1 patient no effect on clinical VT during UA+BA was observed. The follow up lasted 4±3 months. Six (75%) VT patients remained arrhythmia-free and significant PVC burden reduction was achieved in nine (90%) PVC patients during follow-up. One patient treated for electrical storm experienced a single VT episode after 11 months. One patient after initially failed UA+BA underwent successful bipolar reablation after 2 months. Conclusions: Bipolar ablation of refractory ventricular arrhythmias using a novel dedicated adapter is feasible, seems safe and effective. These encouraging preliminary results need to be confirmed in properly designed prospective trials. Funding Acknowledgement: Type of funding sources: None.